PERSEPSI MAHASISWA TERHADAP FASILITAS DALAM WEB BASED LEARNING - Eveline Siregar; Cecep Kustandi (Perspektif Ilmu Pendidikan, 2010)
This study aims at obtaining empirical data about student perceptions on the facilities of Indonesian web based learning at www.courses.web-bali.net developed by the Study Program of Educational Technology, School of Education, State University of Jakarta, and providing input to administrators and policy makers in its development. This study used survey methods of descriptive type. The data were collected by distributing questionnaires directly to 36 students selected as samples of 2008 academic years students who used www.courses.web-bali.net in semester 091 for Management of Information System course. Based on the data and analysis the study concluded that the student perceptions of Web Based Learning is catagorized good.